Toxicological evaluation and anti-inflammatory potential of an ethanolic extract from Bromelia balansae (Bromeliaceae) fruit - da Silva Balin, Paola [UNESP]; Zanatta, Flavia Carina [UNESP]; Jorge, Bárbara Campos [UNESP]; Leitão, Maicon; Kassuya, Roberto Mikio; Cardoso, Claudia Andrea Lima; Kassuya, Cândida Aparecida Leite; Arena, Arielle Cristina [UNESP] (Elsevier, 2018)
Ethnopharmacological relevance: Bromelia balansae is a relatively unexplored medicinal species that is used for nutritional purposes and in folk medicine to treat cough or wounds. Aim of this study: This study assessed the anti-inflammatory activity of the ethanolic extract obtained from Bromelia balansae fruit (EEBB) as well as the toxicological potential of this extract after single and repeated exposure. Materials and Methods: Male rats (Wistar) were gavaged with 2000 mg/kg of extract from the fruit of B. balansae for the acute toxicity test and with 25, 100, or 400 mg/kg of EEBB for the subacute toxicity test. The anti-inflammatory effect of EEBB was evaluated in vivo (30, 100, or 300 mg/kg) by carrageenan (Cg) induced-oedema and pleurisy in Swiss mice. Results: A single oral dose of EEBB did not result in toxicity, demonstrating that the LD50 of this extract was greater than 2000 mg/kg. In the subacute toxicity test, the tested doses produced no significant changes in the haematological, biochemical or histopathological parameters of treated animals. Similarly, there were no statistically significant differences in the sperm parameters. A dose of 300 mg/kg of EEBB significantly reduced oedema formation, Cg-induced mechanical hypersensitivity and cold sensitivity, as well as leukocyte migration in the pleurisy model. Conclusion: These results show that EEBB has an anti-inflammatory potential without causing acute or subacute toxicity. These data may contribute to the advancement of biopharmaceutical applications for this species.
Keywords: Bromelia balansae; Carrageenan; Inflammation; Toxicity